APPLYING TEM MODEL (TEACHING EVALUATION MODEL) IN AN ACADEMIC COURSE IN ACCOUNTING: A COMPARISON ACROSS FIVE YEARS - Ida Verna; Domenico Perozzi (European Scientific Journal, ESJ, 2014)
The research is focused on the performance analysis of students attending an academic course in accounting across five years. The teacher adopted the new methodology so called TEM (Teaching Evaluation Model). In particular, the Teaching Evaluation Model (TEM) is a “work model” used by the professor whit the aim to continuously improve the academic teaching activity through a continuously valuation process of the students and of the teacher itself. The TEM model represents, in summary, a systemic approach to the teaching activity, based on the Deming Cycle (Plan, Do, Check, Act). The scope of the current research is to test the efficacy of the TEM model applied during an academic course in accounting across different years